Evaluating the effectiveness of Scoring Rubrics Assisted Reading (SRAR) technique in the reading of software requirements work documents - Mkpojiogu, Emmanuel O.C.; Hashim, Nor Laily (Medwell Publishing, 2017)
The quality of requirements work products and of software depends on how effective the reading technique and mechanism is. A number of reading techniques have been proposed and in use. These techniques assist in the reading process, in the detection of defects and errors and in the enhancement of the quality of software artifacts. Nevertheless, the effectiveness of a range of reading techniques is at varying degrees. The most familiar and common reading technique is the checklist-based reading technique. This technique, although, it is an enhancement over the ad hoc reading technique is however, bugged with some limitations that affect its usability and effectiveness. It provides too wide-ranging questions to readers without any precise guidance on how they can go about the reading exercise. No previous work has been done on evaluating the effectiveness of SRAR. This study evaluates the effectiveness of the Scoring Rubric-Assisted Reading (SRAR) technique using two metrics: defect density and defect criticality rate. The method used is as follows: the use of SRAR, detection of defects, counting of defects present in the artifacts and refining of the artifact for each round/iteration of review. The defects found by reviewers were counted and presented as averages and percentages. Preliminary result reveals the effectiveness of this technique. SRAR is effective because it is helpful and successful in detecting defects, reducing the amount of defects (including critical defects) in a software artifact and in improving the quality of such software artifact.